Respuesta :

Answer:

8 + i

Step-by-step explanation:

What you need to simplify this is the following "definitions" of i to different powers.

[tex]i^1=i[/tex]

[tex]i^2=-1[/tex]

[tex]i^3=i^2*i=-1*i=-i[/tex]

[tex]i^4=1[/tex]

Now we can sub these in for the various powers of i in our expression:

[tex]6(1)+6(-i)-2(-1)+\sqrt{-1*49}[/tex]

Simplifying a bit:

[tex]6-6i+2+\sqrt{i^2*49}[/tex]

Since we know that the square root of i-squared is i, and that the square root of 49 is 7, we can get rid of the radial sign as follows:

6 - 6i + 2 + 7i

And the final answer, in a + bi form, is

8 + i